Comparison of risk of abdominal hysterectomy versus myomectomy in the management of uterine fibroids: a comparative study - A., Ulagammal; Sanyal, Urmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The incidence of leiomyomas ranges from 20 to 25% in women aged 30 years and above. Gynaecologists prefer abdominal hysterectomy over myomectomy due to a reported recurrence rate of 10% during a 5 year follow-up period. This study aimed to explore the differences in risk between abdominal myomectomy and hysterectomy in treatment of uterine fibroids. Methods: The study was conducted at the department of obstetrics and gynaecology in a tertiary care hospital at puducherry during April 2016 by retrospective analysis of past records like patient charts and operative notes of myomectomies and hysterectomies conducted during the period of May 2013 to March 2016. Those abdominal hysterectomies and myomectomies done for uterine fibroids were included for the study. Results: The study included a total of 145 subjects, 43 among them underwent abdominal myomectomy and 102 underwent total abdominal hysterectomy. There was a significant difference in age (p<0.001) and parity (p<0.001) between the two groups. Most of the anthropometric, intra-operative and post-operative parameters were not much different between the myomectomy and hysterectomy groups. Conclusions: Myomectomy can be preferred over hysterectomy for managing uterine fibroids in young nulliparous and primiparous women who want to preserve their fertility for a pregnancy in the near future, as there is no significant difference in the intra/post-operative morbidity between the two surgeries.